Influência da inclinação das cúspides, tipo de retenção e envelhecimento mecânico na resistência à fratura de coroas metalocerâmicas sobre implantes - Rocha, Cibele Oliveira de Melo [UNESP] (2015)
The aim of this study was evaluate the influence of cusp inclination, type of retention and mechanical aging on fracture strength of implant-supported metal-ceramic (MC) single crowns. To static test, six groups were used (n=10): cemented crowns with 33° standard cusp inclination (SCI) or with 20° reduced cusp inclination (RCI), screwed crowns with screw access hole (SAH) not restored with SCI or RCI and screwed crowns with SAH restored with SCI or RCI. To test aging effect, 4 groups were used (n=20): cemented with SCI or RCI; and screw-retained with SAH not restored with SCI or RCI, in which 50% of specimens of each group were submitted to mechanical aging previously to static test. Crowns of a lower second molar were made on the analog implant external hexagon 5.0 (Biomet 3i, West Palm Beach, FL). The cycling (1.106; 125N; 10Hz) will be performed before the fracture resistance test. The static test was performed in a universal testing machine EMIC DL2000, with load application until porcelain failure. After statistical analysis it was observed that the mean fracture resistance of porcelain showed significant effect (p<0.01), to type of retention (TR) and cusp inclination (CI), respectively. To TR, screwed crowns did not show statistical differences (p>0.05), however, both two showed statistically lower values than cemented. To CI, crowns with SCI showed lower values of fracture resistance. After mechanical aging, TR and CI showed significant effect (p<0.01), with better results to cemented crowns and RCI, respectively. The factor mechanical aging did not show significant effect (p=0.659). According to these results, it was concluded that alone, type of retention and the cusp inclination showed influence on fracture resistance of MC crowns, being cemented crowns and reduced cusps mechanically more resistant against a static and cyclic load. The mechanical aging had no significant... (Complete abstract electronic access below)